A concise review on design and control of structured natural rubber latex particles as engineering nanocomposites. (5th October 2021) - Wichaita, Waraporn; Promlok, Duangkamol; Sudjaipraparat, Narissara; Sripraphot, Supang; Suteewong, Teeraporn; Tangboriboonrat, Pramuan
Graphical abstract: Abstract: In this article, we review the modification of natural rubber (NR) latex into the engineered particles for make use of them in functional nanocomposites. The review focuses on tuning nano-/microstructure and/or composition of NR latex particles by means of surface chemical functionalization, structural modification and incorporation of inorganic nanoparticles (NPs). Due to their polydispersity in size and non-spherical shape with complicated indigenous stabilizers, i.e., proteins and lipids, we first describe the fundamental and common methods for the modification of synthetic polymer latex which become a practical guideline for engineering of NR particles to a variety of designs. Subsequently, the examples of successfully modified NR latex and the involved parameters in the preparation are discussed. The different nature and properties of the modified NR latex compared to the synthetic latex are then depicted. Finally, specific examples of these systems used in a range of applications including nanofillers, controlled releasing materials, textiles, electronics and coatings are demonstrated. The research on modification of NR latex particles would be beneficial to the field of materials science and engineering for the valorization of naturally abundant colloidal polymer to the advanced functional materials in the broader utilization/commercialization in the future.